2021
DOI: 10.3390/brainsci11060701
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Prefrontal Cortex Activity Based on Functional Near-Infrared Spectroscopy Data upon Olfactory Stimulation

Abstract: The sense of smell is one of the most important organs in humans, and olfactory imaging can detect signals in the anterior orbital frontal lobe. This study assessed olfactory stimuli using support vector machines (SVMs) with signals from functional near-infrared spectroscopy (fNIRS) data obtained from the prefrontal cortex. These data included odor stimuli and air state, which triggered the hemodynamic response function (HRF), determined from variations in oxyhemoglobin (oxyHb) and deoxyhemoglobin (deoxyHb) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The use of multichannel configurations in almost all studies can confirm that the presentation of an odor elicits a change in activity, most often an increase in HbO2 concentration, in specific regions such as the orbitofrontal cortex. This is in line with the understanding that the orbital cortex receives direct axonal connections from the primary olfactory cortex (Chen et al, 2021).…”
Section: Interpreting Studies Involving Fnirs and Olfactionsupporting
confidence: 87%
See 3 more Smart Citations
“…The use of multichannel configurations in almost all studies can confirm that the presentation of an odor elicits a change in activity, most often an increase in HbO2 concentration, in specific regions such as the orbitofrontal cortex. This is in line with the understanding that the orbital cortex receives direct axonal connections from the primary olfactory cortex (Chen et al, 2021).…”
Section: Interpreting Studies Involving Fnirs and Olfactionsupporting
confidence: 87%
“…Devices used included the NIRSport NIRx device (Gramlich et al, 2017 ), the Pocket NIRS Duo, DynaSense, by Hamamatsu (Kunihiro et al, 2017 ), the Hb133 by Astem Co. (Yamashita et al, 2022 ), and the HOT-1000, WOT-100 by Neu Systems Inc (Rajagoplan, 2018 ; Tomono et al, 2021 ). The recent development of in-house custom systems for odor research has also shown a tendency toward low channel density, as in the case of Moein et al ( 2020 ) and Chen et al ( 2021 ). The need to combine fNIRS with other wearable systems, particularly virtual reality headsets, may also contribute to lower channel numbers (Kaimal et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using the algorithm proposed in this study, it is possible to identify heartbeat signals more clearly with fNIRS and help track cognitive function, stress levels, and age-related changes [30]. This can be used as auxiliary indicators that can be referenced physiologically and neurologically in the clinical environment and provide a more insightful approach in the development of a big data platform.…”
Section: Discussionmentioning
confidence: 99%